Community-Based Digital Tourism Implementation for Revitalizing Lungun Indah Ecotourism in Banyuwangi: Penerapan Pariwisata Digital Berbasis Komunitas untuk Revitalisasi Ekowisata Lungun Indah di Banyuwangi - Lukman Hakim; Ratri, Arum Andary; Ratri, Indira Nuansa; Rentianto, Tresnarai Juniarizky; Tsuroyya Fillah , Syifa' (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This community service program revitalizes the Lungun Indah riverside attraction in Banyuwangi through a digital-tourism, community-based approach. The intervention integrates (i) physical enhancement—area cleaning, repainting, layout reorganization, and ornamental planting; (ii) safety enablement—provision of life jackets and an inflatable boat to support family-friendly river activities; and (iii) digital capacity building—creation of an official Instagram account, development of a tourism website with a virtual tour, and hands-on training for video promotion and website management involving Digital Business students. Methods followed sequential phases: problem analysis with local stakeholders (Bumdes and village officials), collaborative site improvement, digital content and platform development, training, and evaluation via a short Likert survey administered to Bumdes managers and village officers. Results indicate visible upgrades in cleanliness and aesthetics, improved visitor safety readiness, and stronger online visibility alongside emerging skills for independent content production and website upkeep. Survey feedback shows high acceptance and perceived relevance of the interventions, supporting the feasibility of sustained, locally managed promotion and operations. The program demonstrates that coupling basic physical readiness with targeted digital marketing and community capacity can effectively enhance destination appeal, strengthen governance at village level, and provide a scalable model for rural tourism revitalization.